Science of Translation Today: Change of Scientific Paradigm - Garbovskiy, Nikolay; Kostikova, Olga (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
The present article is devoted to analyzing the present state of the Russian science of translation and its historical perspective. The rationale behind this article is the fact that in Russian academic community there is a persisting viewpoint that research in translation studies is an auxiliary and applied area of linguistics and that science of translation does not exist at all because it is diluted in pluridisciplinary continuum and, which is essential, does not have scientific paradigms. We will attempt to understand whether this opinion is true, and in order to do it we will examine history of scientific knowledge about translation activity and analyze the present state of the discipline that is known at present as “science of translation” in Russia. Thus, the article addresses two intertwined tasks: to prove that Russian theory of translation has scientific paradigms and to characterize research in translation studies in Russia in historical perspective and demonstrate its close interrelation with science of translation in the world.